(3GdYHGH GdRGNQ hGddHGH GdaGNQs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s
(3BNQgG (B:s
(3HdZ GdYQGV HCdg GdPi gh HNWi dbQGAI GHfi CHj GdHQcGJ eMeO GdedbH HGdVjGA , GQGg Gddg eQGTOg , ai GdSGOS YTQ ef TgQ QHjY GdGNQ SJg (B649 (3, hcJH GdUZGfi MGeOkG heUdjkG s
(3hYdjg NW GdeDda HBNQgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B360 s
Keywords: (3GddZIs